Educational Model for Overcoming Stunting Toddlers with Bio Acupressure Massage Using Pure Coconut Oil - Nyoman Ribek; I Gusti Ketut Gede Ngurah; Ketut Labir; Ketut Wardani (Universitas Pendidikan Ganesha, 2021)
Educational models to overcome stunting are needed because stunting has a negative impact on the health and function of the body as well as increasing child morbidity. The prevalence of stunting under five in Indonesia in 2019 was 27.67%, in Bali 21.9% and Karangasem 26.23% above WHO 20%. This data is the reason for conducting research in 2020. The aim is to find out whether the educational model of bio acupressure massage using virgin coconut oil can increase appetite, sleep quality and immune power so that stunting toddlers increase height. The research method is quasi-experimental; the research design is nonequivalent control group design. The sample is 50 people with purposive sampling technique. The analysis before and after treatment was carried out by paired sample t-test, the results were that all variables had significant differences (P value> 0.05). Variable differences between groups using t-two independent test with an alpha of 0.05 resulted in a significant difference in appetite (P value = 0.01) and a significant difference in height (p value = 0.020). There was no significant difference between sleep quality and endurance (P value > 0.05). It was concluded that there was a significant difference before and after education on stunting, while between the bio acupressure and conventional groups there was a significant difference in the variables of appetite and height. It is recommended that in overcoming stunting, bio acupressure massage education is the right education.